1999
DOI: 10.1177/089124399013005005
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Gender in Reality Crime Tv

Abstract: This article focuses on the social construction of femininity in a reality television program, America's Most Wanted. The program blurs fact and fiction in reenactments of actual crimes. The analysis focuses on its depiction of women crime victims. A prior study argues that the program empowers women to speak about their victimization. Other research suggests that such programs make women fearful. The authors compare episodes from the 1988-1989 and the 1995-1996 seasons. Although women spoke about their victim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…In addition, women were portrayed in a stereotypical fashion; they were marked by their physical attractiveness, motherhood, and ''fragile relationships with intimates'' (Cavender et al, 1999, p. 659). This often led to their victimization and to blame for their victimization (Cavender et al, 1999;Surette, 2007).…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, women were portrayed in a stereotypical fashion; they were marked by their physical attractiveness, motherhood, and ''fragile relationships with intimates'' (Cavender et al, 1999, p. 659). This often led to their victimization and to blame for their victimization (Cavender et al, 1999;Surette, 2007).…”
Section: Literature Reviewmentioning
confidence: 98%
“…Dominick's (1973) earlier research is but one example lending support for this notion, as 20% of television victims were female (compared to 16% female offenders). More recently, upon viewing episodes of America's Most Wanted in 1989 and 1997, Cavender et al (1999) found that 50% of the women were ''crime victims.'' It was also noted that women had very few speaking roles and were often at risk of violent crime by the hands of strangers as opposed to loved ones.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar to this distinction between the Final Girl and sexual girls in the slasher film, media constructions of female victims typically classify women into two broad frameworks based on the extent to which they conform to schemas concerning traditional gender roles-the "good girl" and the "bad girl" (Benedict 1992;Finn 1989Finn /1990Eschholz and Bufkin 2001;Hirsch 1994;Meyers 1997). Women whose behaviors fall within the boundaries of traditional or stereotypical gender roles, such as the domesticated mother and wife or the virginal young girl, are constructed in the media as "good girls," "virgins,", or "Madonnas" (Cavender et al 1999;Eschholz and Bufkin 2001). Comparatively, female victims who challenge traditional gender roles-sexually assertive or promiscuous women-are constructed in the media as "bad girls," "vamps", or "whores.…”
Section: The Slasher Genre Of Horror Filmmentioning
confidence: 99%
“…Womens own perceptions of criminality are found to be stereotypical -dominant representations of criminals among all women are those of poor-minority men (Madriz, 1997). Cavender, Bond-Maupin and Jurik (1999) argue that TV imagery associated with women and crime emphasises feminine vulnerability to violence and masculine mastery.…”
Section: Gender Differences In the Structuration Of Crimementioning
confidence: 99%